(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Objective. We aimed to investigate the peculiarities of cardiovascular system parameters and changes in spine sagittal curves with age in schoolchildren and also possible interrelation between parameters in those two systems. Material and methods. 124 schoolchildren (aged 7—18 years) were divided into three groups according to their age. For evaluation of cardiovascular system the bicycle ergometry test with modified Bruce protocol was performed and computerized functional test analysis system “Kaunas — Load” was used. Load, arterial blood pressure, ECG in 12 standard derivations were synchronously recorded at every step. Evaluation of spine sagittal plane was performed using flexible ruler-cirtometer. Angular values of thoracic kyphosis and lumbar lordosis were measured. Results. Parameters of sagittal spine had few differences according to gender and age. Changes in sagittal plane curves with age were greater in boys than in girls. In the group of boys the expression of both sagittal curves had decreasing tendencies with age. Changes in girls’ sagittal curves were inconsistent with age. However, we found many significant differences in the parameters of cardiovascular system’s depending on gender and age. Different correlations between spinal sagittal curves and cardiovascular parameters according to gender and age could beassociated with different state in musculoskeletal system and development, different physical activity level and manyother factors, which vary among girls and boys and also changes with age. Conclusions. There was no significant difference of lumbar lordosis according to gender in all age groups. The thoracic kyphosis had significant different expression only among boys and girls in 7—10 years age group. We found significant difference of such cardiovascular system parameters as index of health, maximal power, pressure rate index, half recovery period of heart rate and change of double product according to gender. Thoracic kyphosis had more correlations with cardiovascular system parameters than lumbar lordosis. Blood pressure reactions had more correlations with spine sagittal curves in older girls and younger boys. Keywords: sagittal spine curves, cardiovascular system, lumbar lordosis, thoracic kyphosis.